Analyzing the role of citizen science in modern research - Ceccaroni, Luigi, 1969-; Piera, Jaume, 1966- (IGI Global, 2017)
"This book focuses on analyzing data on current initiatives and best practices in citizen engagement and education programs across various disciplines by highlighting emergent research and application techniques within citizen science initiatives"--Resumé vydavatele
Na obálce: Premier reference source
Keywords: občanská věda; věda -- sociální aspekty; věda a společnost; vědecký výzkum; občanská angažovanost; spolupráce; science -- social aspects; science and society; scientific research; community involvement; cooperation; kolektivní monografie; collective monographs